Folded–twisted mechanisms control dynamic redox properties, photophysics and electron transfer of anthanthrene-quinodimethanes - Cárdenas Valdivia, Abel; Lirette, Fréderic; Marín-Beloqui, José Manuel; Carreras, Abel; Casanova, David; Boismenu-Lavoie, Joël; Morin, Jean-François; Casado-Cordón, Juan (RSC, 2025)
The synthesis, electrochemical, spectroelectrochemical, photophysical and light induced electron transfer reactions in two new anthanthrene quinodimethanes have been studied and analyzed in the context of dynamic electrochemistry. Their properties are dependent on the interconversion between folded and twisted forms, which are separated by a relatively small energy range, thus allowing to explore their interconversion by variable temperature measurements. The photophysics of these molecules is mediated by a diradical excited state with a twisted structure that habilitates rapid intersystem crossing. Moreover, when codissolved with an electron acceptor compound such as PCBM, direct anthanthrene to PCBM electron transfer and back-electron transfer are also observed, resulting in the formation of charged states and, then, a raise in the population of the excited state triplet manifold upon charge recombination. Some of these properties have been interpreted with the help of quantum chemical calculations. The existence of an equilibrium between folded and twisted states upon electrochemical and photoexcitation stimuli represents a novelty in comparison with existing literature on compounds also showing dynamic electrochemical properties.
Keywords: Electrones - Transporte; Fotoelectricidad; Química física; Folded–twisted mechanisms control; Photophysics; Electron transfer